Simplifying differential equations concerning degenerate Bernoulli and Euler numbers - Qi, Feng; Wang, Jing-Lin; Guo, Bai-Ni (Elsevier, 2018)
In the paper, the authors signiﬁcantly and meaningfully simplify two families of nonlinear ordinary differential equations in terms of the Stirling numbers of the ﬁrst and second kinds.
Keywords: Nonlinear ordinary differential equation; Stirling number of the first kind; Stirling number of the second kind; Bernoulli number; Euler number